ANALISIS IMPLEMENTASI PERATURAN DAERAH KOTA SEMARANG NOMOR 3 TAHUN 2013 TENTANG KAWASAN TANPA ROKOK DI KANTOR KELURAHAN KOTA SEMARANG - Sofia Farahdina; Kusyogo Cahyo; Emmy Riyanti (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2016)
Local Goverment Regulation Number 3 Year 2013 concerning on tobacco free area (KTR) is one of the policies issued by Semarang goverment to control the negative effects caused by smoking activity in which can harm people’s health. The result of this research shows that there are plenty of disobedience in the implementation of the regulation. It was found that smoking activity in the non-smoking areas is still high, particularly in Kelurahan offices. The research took place in Kelurahan offices in Semarang. The aim of this study is to analyze factors related to the implementation of local government regulation Number 3 Year 2013 in Kelurahan offices. Descriptive analytic with cross-sectional approach is used in this study. The population of this study is 177 with 147 Lurah as the sample. Saturated sampling is used in this study. Chi-square test is used to analyze the data with 95% significance. The result of this study indicates that 62,2% of the Kelurahan offices have implemented local government regulation number 3 year 2013 well, while51,7% Kelurahan office have communication well. 59,9% Kelurahan office have had adequate resources, 51,0 % Kelurahan office have good disposition and 95,9% Kelurahan office have good bureaucratic structure. The chi-square statistic shows that there is communication correlation (p = 0,018), resources (p = 0,001), and disposition (p = 0,001) and has no correlation between bureaucratic structure (p = 0,197). Analysis multivariat using regression logistics shows that indicated significant influence between diposition with implementation Local Government Regulation Number 3 Year 2013 concerning on tobacco free area (KTR) (p = 0.001).